Leaf turgor loss point shapes local and regional distributions of evergreen but not deciduous tropical trees. Issue 2 (10th February 2021) - Kunert, Norbert; Zailaa, Joseph; Herrmann, Valentine; Muller‐Landau, Helene C.; Wright, S. Joseph; Pérez, Rolando; McMahon, Sean M.; Condit, Richard C.; Hubbell, Steven P.; Sack, Lawren; Davies, Stuart J.; Anderson‐Teixeira, Kristina J.
Summary: The effects of climate change on tropical forests will depend on how diverse tropical tree species respond to drought. Current distributions of evergreen and deciduous tree species across local and regional moisture gradients reflect their ability to tolerate drought stress, and might be explained by functional traits. We measured leaf water potential at turgor loss (i.e. 'wilting point'; πtlp ), wood density (WD) and leaf mass per area (LMA) on 50 of the most abundant tree species in central Panama. We then tested their ability to explain distributions of evergreen and deciduous species within a 50 ha plot on Barro Colorado Island and across a 70 km rainfall gradient spanning the Isthmus of Panama. Among evergreen trees, species with lower πtlp were associated with drier habitats, with πtlp explaining 28% and 32% of habitat association on local and regional scales, respectively, greatly exceeding the predictive power of WD and LMA. In contrast, πtlp did not predict habitat associations among deciduous species. Across spatial scales, πtlp is a useful indicator of habitat preference for tropical tree species that retain their leaves during periods of water stress, and holds the potential to predict vegetation responses to climate change.